CpG methylation at GATA elements in the regulatory region of CCR3 positively correlates with CCR3 transcription - Uhm, Tae Gi (Korean Society for Biochemistry and Molecular Biology, 2012)
DNA methylation may regulate gene expression by restricting the access of transcription factors. We have previously demonstrated that GATA-1 regulates the transcription of the CCR3 gene by dynamically interacting with both positively and negatively acting GATA elements of high affinity binding in the proximal promoter region including exon 1. Exon 1 has three CpG sites, two of which are positioned at the negatively acting GATA elements. We hypothesized that the methylation of these two CpGs sites might preclude GATA-1 binding to the negatively acting GATA elements and, as a result, increase the availability of GATA-1 to the positively acting GATA element, thereby contributing to an increase in GATA-1-mediated transcription of the gene. To this end, we determined the methylation of the three CpG sites by bisulfate pyrosequencing in peripheral blood eosinophils, cord blood (CB)-derived eosinophils, PBMCs, and cell lines that vary in CCR3 mRNA expression. Our results demonstrated that methylation of CpG sites at the negatively acting GATA elements severely reduced GATA-1 binding and augmented transcription activity in vitro. In agreement, methylation of these CpG sites positively correlated with CCR3 mRNA expression in the primary cells and cell lines examined. Interestingly, methylation patterns of these three CpG sites in CB-derived eosinophils mostly resembled those in peripheral blood eosinophils. These results suggest that methylation of CpG sites at the GATA elements in the regulatory regions fine-tunes CCR3 transcription.